Disobedience of police officers to the constitutional guarantees of children and adolescents - Caraballo, Ysabel; Guzmán, Dorys (Conexiones UG, 2023)
During the last years, great efforts have been made to improve the situation of children and adolescents, if the text of the Organic Law for the Protection of Children and Adolescents is reviewed, it is evidenced in the legal instrument, which does not establishes sanctions for policeofficers in the denial of justice to children and adolescents within the framework of constitutional guarantees, one must resort to what has been established in this regard by the Code of Civil Procedure, which in the investigator’s opinion, the Sanctions prescribed therein are pecuniary.From this perspective, the proposal for a strategic plan for prevention of rape committed by police officers in denial of justice for children and adolescents is raised; deprivation of liberty and punitive measures. Investigative, support was obtained in the qualitative approach, in the feasible project modality, making the respective support in the reading of laws, texts,jurisprudence, comparative legislation, among other printed materials of interest in the matter.In this order of ideas, it is pursued to make practical the pecuniary and civil criminal legislation within the Organic Law for the Protection of Boys, Girls and Adolescents. This proposal is especially addressed to the police officers of the central command of the Bolivarian Police of the State of Aragua.
Keywords: police officers; denial of justice; Boys Girls and Adolescents; citizen security; rape